Cloud computing : Web-based applications that change the way you work and collaborate online - Miller, Michael, 1958- (Que, 2008)
"Cloud computing is a new way to work with programs and data, collaborate with friends and family, share ideas with coworkers and friends, and most of all, be more productive! The "cloud" consists of thousands of computers and servers, all linked and accessible to you via the Internet. With cloud computing, everything you do is now we-based instead of being desktop-based; you can access all your programs and documents from any computer that's connected to the Internet."--Jacket